Dr. B. J. Selman (1934-2009): A Man and a Coordinator - Islam, M Saiful (University Journal of Zoology, Rajshahi University, 2010)
DOI: 10.3329/ujzru.v28i0.5294 Univ. j. zool. Rajshahi Univ. Vol. 28, 2010 pp. 81-82